Sampling techniques - Cochran, William G. (New York : Wiley, 1963)
"This invaluable Second Edition of an incomparable reference/text offers a comprehensive presentation of scientific sampling principles and shows how to design a sample survey and analyze the resulting data - demonstrating the validity of theorems and statements without resorting to detailed proofs." "Citing results from actual large-scale sample surveys in Europe, Asia, Africa, and the United States, Practical Sampling Techniques, Second Edition furnishes a well-organized logical sequence of topics and explains single-stage, stratified single-stage, and multistage sampling, including simple random, systematic, and varying probability sampling as well as self-weighting design. In addition, Practical Sampling Techniques, Second Edition provides entirely new material on the necessity of computers in data processing, analysis, and publication of sample surveys ... internationally sponsored, multicountry survey programs .
Includes bibliographical references and index
aia 03/05/2018
Loans
Keywords: Sampling (Statistics).